USE OF AFLP MOLECULAR MARKERS FOR ESTIMATING GENETIC SIMILARITY OF ALFALFA (MEDICAGO SATIVA L. SL.). - Dobrzycka, Agnieszka; Broda, Zbigniew; Bocianowski, Jan; Ćwiklinska, Anna (Plant Breeding and Seed Science, 2009)
The aim of study was to determine genetic similarity among sixteen alfalfa populations using the AFLP technique. Plant material was selected considering the high genotypic variability. It included populations of different origin: native forms of alfalfa (secondary ecotypes), inbred lines, single hybrids, synthetic populations, varieties and mutants...